Modeling the tumor growth with the theory of discrete fractional calculus - Ramírez Hernández, Leticia; Martínez Ortiz, Juan (Acta Universitaria, 2013)
In this paper we describe the basics of modeling the growth of cancerous tumors, based on the formalism of the calculation of fractional order differences. Version is used in the Gompretz equation of differences, a simulation with arbitrary values of the growth rates of decline and the initial value.